Twenty Years of Harmonisation and Still Divergent: Development of Slovak Competition Law - Ondrej Blažo (Yearbook of Antitrust and Regulatory Studies, 2014)
Since the time when the first competition rules were adopted after the Velvet Revolution in early 1990s, Slovak competition law has undergone several changes. Three acts on economic competition were subsequently adopted (in 1991, 1994, 2001), each of them several times amended. Although Slovakia became a member of the EU in 2004, the convergence of national competition rules with the law of the European Union is evident in the significant changes that were introduced in 2004. The evolution of Slovak competition rules cannot be considered finished – major amendments are expected in 2014. The following paper will analyze in which aspects Slovak competition law is diverging from the rules of the European Union. Court jurisprudence reviewing administrative decisions issued in competition matters is also important in the assessment of the competition law environment. The paper will provide an overview of those features of Slovak competition law that shall be harmonised, as well as reasons for their harmonisations. Yet it must be stressed that European law is not the universal model of convergence and hence the paper will provide thoughts on which features of Slovak competition law might remain country-specific.